A survey on health problems and stereotypic behaviours associated with management of stabled horses - Abu Bakar, Ahmad Naqib (2017)
The management of individual stabled horses in multiple equestrian establishments and the occurrence of health and behavioural problems were assessed in 131 animals. Based on interviews and direct observation of the animals, it was found that 61% of the horses spent less than 19 hours/day in the stalls and 39 % spent more than 19 hours/day. Eighty-five percent exercised regularly, whereas 15 % did not exercise at all. All of the horses were fed with mix feed which consist of commercial concentrates, fibres (hay and chaff) and some were fed with additional supplements. All horses were given four meals daily which the feeding frequency of the mix diet were twice per day (late morning and afternoon) and fibre diet (hay) twice per day (early morning and late evening). However, the timing of the meals were not fixed precisely. Lameness (30%), skin diseases (16%) and colic (9%) were the most cited diseases in the interviews. Thirty percent of horses showed behavioural problems. Each of the management factors did not revealed any association on both occurrence of health and behaviour problems using the chi square test. Research findings would be a useful as a baseline data for further analysis in the future.